Tradisi Mewakilkan Wali Nikah Kepada Habaib Perspektif Antropologi Hukum (Studi Di Kota Pekalongan) - navila, nashrotun; Mubarok (Al-Hukkam: Journal of Islamic Family Law, 2025)
Tradition of delegating marriage guardianship (tawkil wali) to Habaib in Pekalongan from the perspective of legal anthropology. This practice arises not from the absence of a legal guardian (wali nasab), but from a sense of religious reverence and the belief that such delegation brings blessings and spiritual legitimacy to the marriage. The study employs a qualitative method with a sociological-empirical approach, drawing on primary data from interviews with local residents who engaged in the practice. Findings reveal that this tradition is deeply embedded in the community's cultural and religious fabric, recognized as a legitimate form of living law. While normative Islamic law requires a nasab guardian or a judge, in this local context, Habaib are seen as respected religious authorities worthy of receiving such delegation. The tradition serves not only legal-religious functions but also reinforces social harmony and cultural continuity, reflecting the pluralistic nature of legal practice in local Islamic communities.